PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS COLLABORATIVE AND INQUIRY PROBLEM BASED LEARNING (CIPBL) PADA MATERI PERUBAHAN LINGKUNGAN UNTUK MENDUKUNG PEMBELAJARAN MENDALAM - Dea Rorencia Br Tarigan; Putu Budi Adnyana; Ni Putu Sri Ratna Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Biology instruction on environmental change at SMA Negeri 1 Banjar has remained dominated by static PowerPoint slides and one-way lecturing, resulting in low student engagement and a low achievement rate of learning objectives, with only 18.2% of students reaching the minimum learning-achievement criterion. This study aimed to produce a valid and practical interactive learning medium based on Collaborative and Inquiry Problem Based Learning (CIPBL) on the topic of environmental change to support deep learning among tenth-grade students. This research and development study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observation, interviews, and questionnaires, then analyzed descriptively using qualitative and quantitative approaches. Product validity was analyzed using the Gregory index, while practicality was analyzed using descriptive percentage analysis. The resulting product is an interactive Google Sites-based website that consistently integrates the five stages of the CIPBL syntax (problem orientation, problem formulation, investigation, presentation of findings, and evaluation) across three sub-topics. Validation by two content experts and two media experts yielded mean percentages of 95.83% and 99.29%, respectively, both categorized as highly valid. Practicality trials involving individual testing, small-group testing, and teacher-practitioner testing yielded 89.12%, 88.21%, and 96.15%, respectively, all categorized as highly practical. These findings indicate that the developed CIPBL-based interactive medium is feasible for use as an alternative Biology learning medium that supports deep learning on the topic of environmental change.